2014
DOI: 10.1021/nn4063853
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Recoverable, Thermostable, Hydrophobic DNA/Silica Encapsulates and Their Application as Invisible Oil Tags

Abstract: A method to encapsulate DNA in heat-resistant and inert magnetic particles was developed. An inexpensive synthesis technique based on co-precipitation was utilized to produce Fe2O3 nanoparticles, which were further functionalized with ammonium groups. DNA was adsorbed on this magnetic support, and the DNA/magnet nanocluster was surface coated with a dense silica layer by sol-gel chemistry. The materials were further surface modified with hexyltrimethoxysilane to achieve particle dispersibility in hydrophobic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 38 publications
2
114
0
Order By: Relevance
“…[48] In an more advanced application, DNA comprising particulate tracers have also been used for understanding the animal-to-animal transfer in food chains, [49] the behavior of silica nanoparticles in sewage plants [50] and in in vitro cell cultures.…”
Section: Chemical Sequence Encoding Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[48] In an more advanced application, DNA comprising particulate tracers have also been used for understanding the animal-to-animal transfer in food chains, [49] the behavior of silica nanoparticles in sewage plants [50] and in in vitro cell cultures.…”
Section: Chemical Sequence Encoding Strategiesmentioning
confidence: 99%
“…In practical applications, tracers with a low detection limit are only suitable when they are homogeneously distributed in the final material. In liquid products encoded particles at a concentration range of ppb can be directly incorporated by dilution series and intensive mixing [47,48]. In the formation of polymer-based products, the need for homogeneous mixtures is not a novel problem, and commonly arises when a polymer is dyed with pigments.…”
mentioning
confidence: 99%
“…However, encapsulation of nucleotides within silica microbeads [44] or plant materials [45] may be carried out in order to protect against this potential degradation.…”
Section: Dna Taggantsmentioning
confidence: 99%
“…Recent work has tested the usage of such tags in the food supply chain by delivering exogenous DNA fragments within a coat of silica, a common food additive, at an extremely low cost. It has been shown that these tags could be used to trace the source of milk in dairy products such as yogurt (Bloch et al 2014) and serve as a long-term authentication mark of premium olive oil (Puddu et al 2014). Moving forward, artificial DNA labels can create an edible data structure that includes the type of food, producer, lot number, nutrient information, and presence of known allergens or simply encode a URL to a webpage that contains this information.…”
Section: Food Industrymentioning
confidence: 99%